Peranan Partai PDI Perjuangan Dalam Membangun Etika Politik: - Yusril Ihza Mahendra; Padli Alfitra; Maulana Muhammad Yahya; Rahmadi Efendi Pane; Indra Harahap (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2023)
Political ethics is not only related to the behavior of politicians, but also related to the practice of social, cultural, legal, political and economic institutions. It can be said, political ethics is related to all aspects of people's lives. The behavior of politicians is only one dimension of political ethics. Political ethics has three dimensions, namely goals, means and political action. The goal dimension prioritizes the attainment of social welfare and a peaceful life based on freedom and justice. Judging from the type of research, there is also the type of research used in this research, namely bibliography research or library research, which is research that is carried out by collecting information or making objective records that mean the object of research or collecting information that has the character of a bibliography, or analysis carried out to unravel a problem which is basically based on critical and in-depth analysis of relevant literature materials. This research results that the relationship and existence of political parties with political ethics is very urgent. The PDI PDI Perjuangan Party is determined to make itself a modern party that maintains its identity as a People's Party by sticking to the principles of sovereignty in the political field, being independent in the economic field, and having a personality in culture. Keywords: Political Ethics, Role, PDI-P